Optimalisasi Penerapan Online Check In Pada Maskapai Citilink Di Bandar Udara Internasional Husein Sastranegara Bandung - Luxyantri Oktamiraz; Gallis Nawang Ginusti (Journal of Creative Student Research, 2023)
Online check in is an online service check in for passengers by their personal smartphone that can be done anywhere within a maximum of 30 minutes before flight. In its implementation, passengers of Citilink Airlines at Bandung Husein Sastranegara International Airport still have several problems when using this service that leads to the implementation of online check in is not optimal. The purposes of this study are to examine: 1) The constraints experienced by passengers when traveling online check in, 2) Efforts to optimize implementation of online check in. This study uses a qualitative method with a descriptive approach. Data collection was carried out through observation techniques, interviews, literature studies, and documentation. To prove the validity of the research data, source and method triangulation tests were carried out. The results showed that the common problems experienced by Citilink Airlines passengers at Bandung Husein Sastranegara International Airport when using online check in are unstable signal, error on website, fault input of booking code and the passenger's last name, as well as the passenger's lack of understanding and enthusiasm for the online check in itself. Based on these problems, the optimization efforts undertaken include the provision of wifi at airports, diversion from online check in to check in counter, as well as more active education from officers to passengers about online check in.